2020
DOI: 10.21608/ejvs.2020.20516.1141
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Profiles of Antibiotic Resistance and Virulence Markers of The Escherichia coli O157 Bacteria Recovered From Poultry Meat

Abstract: E scherichia coli (E. coli) O157 issubstantial foodborne pathogen. The existing survey was addressed to assess the incidence, phenotypic resistance profile and incidence of virulence markers amongst the E. coli O157 isolates recovered from poultry meat. Five-hundred poultry meat samples were collected from Isfahan, Iran.Poultrymeatsamples were cultured and phenotypic antibiotic resistance pattern was deliberated using disk diffusion. PCR was applied to identify the incidence of virulence markers. Forty-four ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…E. coli strains are utilized as sentinel organisms for the surveillance of AMR with gram-negative resistance characteristics and as indicators of fecal contamination of food items since they are common in humans, animals, the environment, and foods (WHO, 2017). Regarding with the obtained results of E. coli sensitivity test (Tables 6 to 8), it came in the same line with those recorded by Kim et al (2020), who recorded a significant resistance of E. coli to ampicillin (69.1%) and tetracycline (64.0%); Mousavi et al (2020) where their E. coli isolates exhibited resistance against ampicillin (95.45%), tetracycline (88.63%), gentamycin (84.09%) and Sulfa/trimethoprim (38.63%) antibiotics, while were sensitive to chloramphenicol (72.73%). Mensah et al (2022) recorded that all of their examined E. coli isolates were sensitive to gentamicin and cefotaxime.…”
Section: Discussionsupporting
confidence: 88%
“…E. coli strains are utilized as sentinel organisms for the surveillance of AMR with gram-negative resistance characteristics and as indicators of fecal contamination of food items since they are common in humans, animals, the environment, and foods (WHO, 2017). Regarding with the obtained results of E. coli sensitivity test (Tables 6 to 8), it came in the same line with those recorded by Kim et al (2020), who recorded a significant resistance of E. coli to ampicillin (69.1%) and tetracycline (64.0%); Mousavi et al (2020) where their E. coli isolates exhibited resistance against ampicillin (95.45%), tetracycline (88.63%), gentamycin (84.09%) and Sulfa/trimethoprim (38.63%) antibiotics, while were sensitive to chloramphenicol (72.73%). Mensah et al (2022) recorded that all of their examined E. coli isolates were sensitive to gentamicin and cefotaxime.…”
Section: Discussionsupporting
confidence: 88%
“…This could explain the severe pathogenicity of these stains and underline the role of quails in transmission of antibiotic resistance bacteria to humans. Previous studies also reported the presence of virulent and antibiotic resistant E. coli strains in poultry meat (Ammar et al, 2015;Himi et al, 2015;Eid et al, 2016;Prihtiyantoro et al, 2019;Mousavi et al, 2020).…”
Section: Disscusionmentioning
confidence: 84%
“…The main reasons for the interest in poultry meat are its relatively low production costs and the absence of cultural and religious restrictions on its consumption [10]. Contamination of poultry meat can occur at various stages of its slaughter and processing [11,12]. Studies have shown that H. pylori can survive in the gastrointestinal tract of chickens, and these bacteria can be present in their feces [13].…”
Section: Introductionmentioning
confidence: 99%